Research on the Impact of Atmospheric Environment Self-Purification Capacity on Fog-Haze Pollution - Jingkun Zhou; Yating Li; Xiao Zhao; Ting Yin (Atmosphere)
Why is fog-haze pollution very serious in Hebei province, where there are many pollution-intensive industries, and in Guangdong province, where it is not so serious? This paper uses the spatial Durbin model, the threshold effect model, and relevant local city data, etc., to explore the effect of the atmospheric environment’s self-purification capacity on haze pollution from the perspective of green technology innovation. We found that the great haze outbreak in China is due to the large amount of ultrafine-particle low-cost emissions caused by the haze detection by weight method implemented in 2011 and 2012. This study also found that haze pollution in China has a significant impact on the atmospheric environment’s self-purification capacity. The atmospheric environment’s self-purification capacity has an inhibitory effect on haze pollution. When green technology innovation reaches the first threshold, the atmospheric self-purification capacity can significantly reduce the impact of haze pollution. When green technology innovation reaches the second threshold, the atmospheric self-purification capacity to reduce haze pollution is significantly enhanced. China’s local haze pollution is serious due to the industrial layout being unreasonable, caused by high-pollution industries emitting particles beyond the limits of atmospheric environment self-purification capacity. Industries in Hebei Province and Guangdong Province are more pollution-intensive, and haze pollution in Hebei Province is serious due to the weak self-purification capacity of the atmospheric environment. Guangdong Province’s atmospheric environment self-purification capacity is strong, and its haze pollution is not serious. Given the scientific use of atmospheric environment self-purification capacity and regional differences in green technology innovation, the development of targeted green input and atmospheric self-purification capacity enhancement policies in areas with serious air pollution, along with green technology innovations based on a region with less pollution, would be beneficial. To increase the amount of green technology innovation investment in regions where the atmospheric environment is not seriously polluted and green technology innovation is based on a bad region, more green funds should be invested in the atmospheric environment’s self-purification capacity. In regions where the atmospheric environment is not seriously polluted and the foundation of green technology innovation needs improvement, more green funds should be invested into atmospheric environment self-purification capacity to fully harness its inhibition of haze pollution. This should be accompanied by scientific planning and adjustments to the high-pollution industrial layout, etc., to effectively enhance the self-purification capacity of the regional atmospheric environment. In addition, the gradient transfer of high-pollution industries should be implemented based on atmospheric environment self-purification capacity to effectively reduce the impact of haze pollution.